The Seismic Design Handbook 2001
DOI: 10.1007/978-1-4615-1693-4_10
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Design of Reinforced Concrete Structures

Abstract: Abstract:This chapter covers various aspects of seismic design of reinforced concrete structures with an emphasis on design for regions of high seismicity. Because the requirement for greater ductility in earthquake-resistant buildings represents the principal departure from the conventional design for gravity and wind loading, the major part of the discussion in this chapter will be devoted to considerations associated with providing ductility in members and structures. The discussion in this chapter will be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It has been suggested that, if RC moment frames cannot satisfy the same criteria as those specified for steel moment frames belonging to the same category (special/ intermediate/ ordinary), suitable adjustments should be made. That is, reducing the values of the R-factor assigned to RC moment frames, allowing a reduction in the required ductility; otherwise, detailing requirements for them should be appropriately enhanced [Derecho and Kianoush, 2001].…”
Section: Research Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that, if RC moment frames cannot satisfy the same criteria as those specified for steel moment frames belonging to the same category (special/ intermediate/ ordinary), suitable adjustments should be made. That is, reducing the values of the R-factor assigned to RC moment frames, allowing a reduction in the required ductility; otherwise, detailing requirements for them should be appropriately enhanced [Derecho and Kianoush, 2001].…”
Section: Research Objectivesmentioning
confidence: 99%
“…A substantial loss in the strength and/or stiffness of beam-column connections due to joint shear distress and/or excessive bond slip may lead to undesirable responses of the frame, such as significant lateral displacements and consequent frame instability and failure due to P-delta effects. Thus, proper detailing should be provided for beamcolumn joints so that beams and columns framing into the joint can develop and maintain their strength and deformation capacity under design-level seismic forces [Derecho and Kianoush, 2001]. …”
Section: Past Experimental Studies On Rc Beam-column Connectionsmentioning
confidence: 99%
“…Immediate occupancy requirements can be achieved by aiming an elastic seismic response. Two possible structural solutions are investigated: 1) a stiffening design approachexpecting high response acceleration and damage (Moehle, 2014;Derecho et al, 2001;Fajfar, 2018;Postelnicu et al 2012) and 2) base isolation (Mazza et al, 2018;Reddy et al, 2019;Sorace et al, 2014).…”
Section: Introductionmentioning
confidence: 99%